The Effect of Political Communication on European Financial Markets during the Sovereign Debt Crisis - Christian Conrad; Klaus Ulrich Zumbach (University of Heidelberg, Department of Economics, 2012)
We quantify all statements by major European politicians reported by Reuters during the August 2011 to December 2011 period and show that political communication significantly affects European stock and bond markets as well as the EUR-USD exchange rate. Communication with respect to Italy induces the strongest market reactions. Financial markets consider the German bondmarket a safe haven.
urn:nbn:de:bsz:16-heidok-142207
Keywords: 330